Activation of Monocyte and Granulocyte Antibody-Dependent Cytotoxicity by Phorbol Myristate Acetate - Klassen, David K. (1982)
We have characterized the effects of phorbol myristate acetate (PMA) on human monocyte and neutrophil oxidative metabolism and antibody-dependent cytotoxicity toward anti-D sensitized human erythrocytes (RBC) and a human lymphoblastoid cell line (CEM). Hexose monophosphate shunt activity was measured by [1-(14)C]glucose oxidation and target lysis by (51)Cr release. PMA produced a dose-dependent stimulation of hexose monophosphate shunt activity. Neutrophils responded with higher hexose monophosphate shunt activity and at a lower PMA concentration than did monocytes. PMA increased monocyte lysis of antibody-sensitized RBC by two-thirds, but did not affect lysis of CEM targets. Neutrophils were unable to lyse either antibody-sensitized or nonsensitized RBC without the addition of PMA. When PMA was added, lysis of both targets increased markedly. Neutrophils without PMA were able to lyse a small number of both antibody-sensitized and nonsensitized CEM targets. PMA also increased neutrophil lysis of these targets. Target lysis by neutrophils from a patient with chronic granulomatous disease, cells unable to produce reactive oxygen species, was not increased by PMA. Chronic granulomatous disease monocytes, however, responded to PMA by more than doubling lysis of antibody-sensitized RBC. Hypoxia inhibited PMA augmentation of antibody-sensitized RBC lysis by neutrophils, but not by monocytes. Generation of reactive oxygen species by the xanthine-xanthine oxidase system inhibited CEM growth, but did not cause lysis, indicating that in some cases oxidative injury may be nonlytic. We suggest that PMA augments neutrophil cytotoxicity to tumor and RBC targets by stimulating reactive oxygen species-mediated lysis, but in monocytes augmentation of lysis is due to activation of a nonoxidative mechanism of lysis.